The Effect of Pregnancy Class on Mothers’ Knowledge Regarding Pregnancy - Adisti; Shinta Novelia; Milla Evelianti (Health and Technology Journal (HTechJ), 2024)
A mother's lack of knowledge about pregnancy will affect the mother's health status. So promotional efforts, one of which is holding classes for pregnant women, are really needed. The aim of this research was to determine the effect of pregnant pregnancy class on mothers' knowledge about pregnancy. The design of this study is quasy experimental. The population is all pregnant women who visited Mekarsari Health Centre during the study period. 15 pregnant women were recruited as the sample purposively with a gestational age between 20-32 weeks. The results found that pregnant women's knowledge is significantly higher than before the implementation of the pregnancy class. The conclusion of the research results is that there is a difference in the level of knowledge of pregnant women about pregnancy before and after carrying out classes for pregnant women at the Mekarsari Health Center, Tambun Selatan District, so it is recommended that the development and monitoring of the implementation of maternal classes be better across programs and across sectors and it is hoped that midwives can carry out the classes.